2017
DOI: 10.1111/iju.13387
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a “low‐risk” cohort of grade group 2 prostate cancer patients: Results from the Shared Equal Access Regional Cancer Hospital database

Abstract: Among men with prostate-specific antigen ≤10 ng/mL and clinical stage T1c/T2a, those in grade group 2 with ≤2 total positive cores have similar rates of adverse pathology and biochemical recurrence as men with grade group 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Sauter et al 2 studied a large historical RP cohort (2005–2014) and demonstrated that there were different likelihoods of BCR in GG2 and GG3 disease correlating with GP4% 2 . However, it is the mere presence of GP4 that significantly increases the probability of adverse surgical outcomes and imparts a metastatic potential relative to pure Gleason pattern 3 (GG1) cancer 1,4,7,32 . For example, none of our GG1 TNs regardless of TV demonstrated SV invasion which is similar to our prior study performed on a cohort from a different institution 33 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Sauter et al 2 studied a large historical RP cohort (2005–2014) and demonstrated that there were different likelihoods of BCR in GG2 and GG3 disease correlating with GP4% 2 . However, it is the mere presence of GP4 that significantly increases the probability of adverse surgical outcomes and imparts a metastatic potential relative to pure Gleason pattern 3 (GG1) cancer 1,4,7,32 . For example, none of our GG1 TNs regardless of TV demonstrated SV invasion which is similar to our prior study performed on a cohort from a different institution 33 .…”
Section: Discussionsupporting
confidence: 78%
“…A recent publication on prostate biopsy specimens suggested that there are similar clinical outcomes for patients with GG2 disease characterized by limited TV and GP4% as for those with GG1 disease. 1 Another study showed that there was no significant difference in time to BCR for GG1 and GG2 cancer when GP4% was less than 6% in biopsy specimens. 3 | 869 likelihoods of BCR in GG2 and GG3 disease correlating with GP4%.…”
Section: Discussionmentioning
confidence: 99%
“…As the percentage of Gleason pattern 4 is currently being reported in the diagnosis, a number of research studies have been carried out to establish a category of patients with a ‘favourable’ prognosis who would benefit from AS. So far, these studies have found that patients with ‘favourable’ Gleason 3 + 4 = 7 (GrG2) still have a higher risk of Gleason grade 4 + 3 = 7 (GrG), EPE, and seminal vesicle invasion at RP, and a higher risk of BCR, than low‐risk men undergoing RP . These studies were performed without consideration of the percentage of Gleason pattern 4 or the different subtypes of Gleason pattern 4, which might have clinical implications for the evaluation of candidates with potential insignificant cancer in the setting of a minor Gleason pattern 4 component …”
Section: Significant Prostate Cancer At Rpmentioning
confidence: 99%
“…So far, these studies have found that patients with 'favourable' Gleason 3 + 4 = 7 (GrG2) still have a higher risk of Gleason grade 4 + 3 = 7 (GrG), EPE, and seminal vesicle invasion at RP, and a higher risk of BCR, than low-risk men undergoing RP. 38,39 These studies were performed without consideration of the percentage of Gleason pattern 4 or the different subtypes of Gleason pattern 4, which might have clinical implications for the evaluation of candidates with potential insignificant cancer in the setting of a minor Gleason pattern 4 component. 40 Another important consideration in establishing the significance of prostate cancer at RP is the presence of a tertiary pattern.…”
Section: T U M O U R G R a D E I N S I G N I F I C A N T C A N C E R mentioning
confidence: 99%
See 1 more Smart Citation